1085 Cardiovascular Dysfunction in Infants with Neonatal Encephalopathy in the 1st Week of Life. (October 2012) - Armstrong, K; Sweetman, D; Franklin, O; Molloy, E
Abstract : Background and Aims: Perinatal asphyxia may result in transient myocardial ischameia, confirmed by elevated Troponin T levels. Gold standard echocardiographic measures of contractility (ejection and shortening fraction) may not pick up subtle ischaemic changes. Tissue Doppler imaging (TDI) allows assessment of systolic and diastolic function. Used in conjunction with Troponin T TDI may offer superior measure of myocardial contractility. Methods: Term infants with evidence of Neonatal Encephalopathy (NE) underwent echocardiography on Day 1 & 7 of life. Healthy term controls had one echocardiogram on Day 1. Serum Troponin T levels were recorded in infants with NE. Myocardial velocities were obtained using a pulsed wave doppler from an apical four chamber view. Peak systolic (S'), early diastolic (E') and late diastolic (A') velocities were recorded. Results: 17 patients with evidence of NE and 20 term controls were recruited. Mean birthweight (SD) was 3.6 kg (0.9) and gestation 39 (5) weeks. TDI systolic and diastolic velocities increased between Day 1&7 in infants with NE. All day 1 measures in the NE group were less than the controls. There was no significant difference between the shortening/ejection fraction on day 1 between the two groups (NE: 33.7–35.3%; Control: 64.3–67.4%) Troponin levels were significantly elevated on Day 1 compared to Day 7 in NE group (p<0.05) (0.53–0.38ng/ml). Conclusions: TDI measures in infants with NE are less than controls on Day 1. Troponin levels were initially significantly increased providing further evidence of myocardial ischaemia in infants with NE.